Enhancing Space Resilience Through Non-Materiel Means - McLeod, Gary (RAND Corporation, 2016)
Space is now a congested, contested, and competitive environment. Space systems must become more resilient to potential adversary actions and system failures, but changes to space systems are costly. To reduce costs, the Air Force asked RAND to identify non-materiel means-doctrine, organization, training, leadership and education, personnel, facilities, and policy-to enhance space resilience over the near and far terms.